Calidad sanitaria del huevo para el consumo humano - O'Farrill, O.
(Es, En)
Ilus., 13 ref.
Keywords: AVES DE CORRAL; CALIDAD; HUEVOS; SALMONELLA; BACTERIOLOGIA; SALUD PUBLICA; AVICULTURA; CUBA; REVISTA CUBANA DE CIENCIA AVICOLA